The effects of removing barriers to equity issuance - Gustafson, Matthew T.; Iliev, Peter (Journal of Financial Economics, 2017)
We study the consequences of a US deregulation allowing small firms to accelerate their public equity issuance. Post-deregulation, affected firms double their reliance on public equity and transition away from private investments in public equity compared to similar untreated firms. The net effect is a 5.7 percentage point or 49% increase in the annual probability of raising equity. This is accompanied by a reduction in equity issuance costs, an increase in investment, and a decrease in leverage. Our findings provide evidence that reducing equity issuance barriers benefits issuers even in highly developed markets.